Familial chylomicronemia: A rare case report - Sowjanya, S V N S; Lakshmi, V; Thiagarajan, Karthik (Indian Journal of Case Reports, 2020)
We report a 5-day-old neonate born out of 3rd-degree consanguinity who presented with milky blood, hepatosplenomegaly, and lipemia retinalis (fundus examination). The baby was asymptomatic, euglycemic, and did not have xanthomas. Lipid profile was altered (total cholesterol - 2340 mg/dl, triglycerides (TG) - >10,000 mg/dl, high-density lipoprotein -